Removal of iliosacral screws: the washer problem. Issue 10 (October 2021) - Gani, Muhammad Haseeb; Ward, Jonathan; Arshad, Homa; Culpan, Paul; Bates, Peter
Abstract: Iliosacral screw removal is an infrequent surgery, and when needed, removal of the washer can be surprisingly difficult. Different forceps, clamps and other non-specific instruments are frequently used to this end, many a time without success, or at the expense of tissue damage, blood loss and radiation exposure. After trying all the tricks in the book, we devised this neat little surgical tactic that ensures easy and reliable retrieval of the washer when removing iliosacral screws percutaneously, with no increased morbidity.